Management Accounting Practices in the Public Sector: Systematic Analysis of Social, Economic and Environmental Impacts - Cahyani Putri Ayu; Jeanne Adelina Savitri; Luk Luk Fuadah (Dinasti Publisher, 2025)
Public sector management accounting has evolved from an administrative function into a strategic instrument that enhances efficiency, accountability, and sustainability in governance. This study systematically analyzes the impact of Management Accounting Practices (MAPs) on the social, economic, and environmental dimensions of the public sector. Using the Systematic Literature Review (SLR) method based on PRISMA guidelines, 37 Scopus-indexed articles published between 2015 and 2025 were reviewed. The findings reveal that MAPs improve resource efficiency and budget effectiveness (economic aspect), strengthen accountability and public participation (social aspect), and support the implementation of sustainability accounting and green governance (environmental aspect). Digital transformation further enhances MAPs through data-based reporting and transparent performance monitoring. However, bureaucratic resistance, limited resources, and political influence remain major challenges in developing countries. Overall, MAPs serve as a strategic foundation for achieving efficient, accountable, and sustainable public sector governance.